X-ray diffraction analysis of the polymorphic transition of lead oxide in a polymer matrix formed in constant physical fields - Vilensky, V. O.; Bardadym, Y.V.; Gomza, Y.P.; Kercha, Y.Y. (Reports of the National Academy of Sciences of Ukraine, 2014)
The influence of physico-chemical factors at forming the three-dimensional network of a thermosetting plastic under the simultaneous action of constant physical fields upon the crystalline β-form of PbO is first studied. X-ray structural analysis of composites on the base of polyepoxy-lead monoxide and polyaniline showed the formation of a new crystal ϕ-phase.Constant physical fields and polyaniline intensify the processes of condensation and crystallization of the formed phase. It is established that the crystallization of the ϕ-phase occurs under the simultaneous action of physical fields and polyaniline and each factor independently.